2022
DOI: 10.21608/ejabf.2022.260722
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dietary fish oil: soybean oil ratios on growth performance feed utilization, haematological indices and body fatty acid composition of Keeled mullet, Liza carinata fingerlings

Abstract: the nutritional strategies developed to bridge the gap between supply and demand for animal protein from seafood, but this development must be sustainable (Aboseif et al., 2022 a,b; Flefil et al., 2021). Fats are important in the aquaculture feed industry, as they are the main source of essential FA and provide energy for fish (Wang et al., 2022; Zorlu et al., 2022). Fish oil (FO) is the primary ideal lipid source in aquatic feeds which is high in n-3 long-chain polyunsaturated fatty acids (n-3LC-PUFA) such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The results showed that the apparent IMTA-FCR was 0.90, which is better than the industry standard FCR of 1.50 for intensely commercial tilapia or cat sh monoculture systems 38,49,50 . As a result, the IMTA system appears to be one of the most important strategies to boost feed utilization in aquaculture.…”
Section: Discussionmentioning
confidence: 80%
“…The results showed that the apparent IMTA-FCR was 0.90, which is better than the industry standard FCR of 1.50 for intensely commercial tilapia or cat sh monoculture systems 38,49,50 . As a result, the IMTA system appears to be one of the most important strategies to boost feed utilization in aquaculture.…”
Section: Discussionmentioning
confidence: 80%
“…This understanding can lead to the development of more efficient fish capable of utilizing new diets, ultimately improving fish nutrition in the future. By focusing on the nutritional programming of metabolism linked to the early life stages of fish, we can also contribute to the development of sustainable aquaculture practices (Panserat et al, 2019; Aboseif et al, 2022aAboseif et al, , 2022bAboseif & Goda, 2022). Furthermore, the nutritional programming could be employed as a strategy in aquaculture to promote sustainable feeding strategies (Hou & Fuiman, 2020).…”
Section: Fish Nutrition Chitosan Nanoparticles Nanotechnology Nile Ti...mentioning
confidence: 99%